Utilisation and conservation of arenga species using the community based natural resource management (CBNRM) aprroach - Tu, Chu Lee (Universiti Malaysia Sarawak (UNIMAS), 2015)
There are 13 varieties of Nyok that have been recognised by the community at Kiding village. The documentation and utilisation of the Nyok varieties however, are yet to be studied. Furthermore, the conservation work on Nyok by the local community is less known. This study focused on the sustainability potential by accessing the species diversity, relative density and relative frequency in different forest types namely agroforestry area, rubber plantation and secondary forest. This study also focused on the viability and sustainability of Nyok in the production of local wine and the value to ensure the current demand can be sustained The result showed that only one species of Arenga has been identified from 13 varieties of Nyok. The recognition of Nyok by the community is based on the interaction with the conditional of the environment, surrounded plant, soil types and insect. Agroforestry has the highest number of Nyok varieties compared to rubber plantation and secondary forest. The population of Nyok in Kiding village is under threat due to the lost of interest from young generation. The knowledge in making Ijuk is disappearing even though Nyok is still planted and conserved by the old generation. The studies on Nyok population and its conservation effort should be emphasised as this palm can be one of the modeling plants for conservation and value creation.